COPD as a risk factor for carotid artery disease (CAD) and low-extremity artery disease (LEAD) - Buklioska Ilievska, Daniela; Minov, Jordan; Kochovska Kamchevska, Nade; Baloski, Marjan; Poposki, Bozidar (European Respiratory Society, 2020)
We aimed to investigate the association between COPD and peripheral artery disease (PAD), the relation to the severity of airflow limitation and the level of serum C-reactive protein (CRP). Cross-sectional study including 120 patients with initially diagnosed COPD, aged 40 to 75 years and 60 non-COPD subjects matched by age, smoking status, body mass index, as controls. All study participants underwent pulmonary evaluation (dyspnea severity assessment, baseline and post-bronchodilator spirometry, gas analyses, chest X-ray), Doppler ultrasonography and measurement of serum CRP. Results presented statistically significant difference in presence of LEAD in COPD patients compared to controls (78.3% vs 38.3%; P<0.001). According to the Fontaine classification, COPD patients with LEAD were categorized in stages I, IIA and IIB (60%, 30% and 15%, respectively), whereas all controls with LEAD were in the Fontaine stage I. COPD patients with LEAD presented significant association between disease severity and clinical manifestations due to the vascular changes (P=0.001) and CRP (P<0.05). Comparison between presence of CAD in COPD and controls showed statistical significance (70% vs 36%; P < 0.0001). The mean value of intima-media thickness (IMT) in COPD patients with CAD was significantly higher than its mean value in controls (0.8 ± 0.2 vs. 0.6 ± 0.1; P=0.0043). IMT value in COPD patients with CAD was significantly related to FEV1 decline (P=0.000) and CRP (P=0.001). We found higher prevalence and severity of PAD in COPD patients compared to non-COPD and significant relation to FEV1 decline and serum CRP. Our findings suggest a need for early screening for PAD in COPD and an integrated-care approach.
Keywords: COPD; COPD - management; Comorbidities